Board effectiveness and company performance: Assessing the mediating role of capital structure decisions - Md Kassim, Aza Azlina; Ishak, Zuaini; Abdul Manaf, Nor Aziah (Universiti Malaysia Sarawak, 2013)
This study examines the mediation effect of capital structure decisions on the relationship between board process and company performance in Malaysia.The study uses two types of data; a questionnaire survey of Malaysian directors and the companies’ annual report.Based on 175 public listed companies, the study finds that effective independent directors and boards who monitor company risks vigorously are more likely to monitor management from adopting excessive leverage, which results in positive company performance.Overall findings are expected to serve as a basis for more effective corporate governance policies and practices in Malaysia in ensuring the sustainability of the listed companies.